SOME ISSUES ON THE SOCIO-ECONOMIC CONTENT OF THE STATE BUDGET AND ITS IMPORTANCE IN SUSTAINABLE DEVELOPMENT (International Journal of Innovative Technologies in Economy, 2020)
The article discusses the state budget, its economic significance and the importance of budget expenditures for sustainable development. At the same time, a literature review on the formation of the state budget was conducted, and foreign experience was studied. The next section of the article describes in detail the formation of the state budget in Azerbaijan, the dynamics of development and the impact of budget expenditures on sustainable development and makes relevant generalizations.At the same time, the article also reflects the trends in the human development index in Azerbaijan as a result of measures taken at the expense of budget expenditures.